Investigation of the presence of bioactive, phenolic and mineral compounds in foods analogous to the cheese based on baru almonds for the public vegan - de Carvalho, Ariella Menegucci; Lamounier Campidelli, Marina Leopoldina; Rocha, Renata Abadia Reis; Carneiro, João de Deus Souza; de Souza, Ellen Cristina; Vilas Boas, Eduardo Valério de Barros (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2022)
In order to broaden the knowledge about the functional potential of baru almond in new vegan products, the present study sought to perform a chromatographic and spectrophotometric characterization of the presence of bioactive compounds, profile of phenolic compounds, physicochemical composition and minerals composition, of the sensorial profile and microbiological characteristics of foods analogous to the cheese based on baru almonds with different types of food condiments. Two formulations of vegetable food analogous to the baru almond based cheese were developed, differing only by the raw materials used for seasoning (AV1 - with pepperoni and oregano, and AV2 - with onion and garlic). Among the main results, Ten types of phenolic compounds were found, among them the presence of gallic acid, and the rutin, in addition, they showed high index of dietary fibers, lipids, calcium, iron, zinc and suitable characteristics microbiological and sensory in AV1 and AV2. Thus, it is understood that it is possible to develop cheese-type products using only vegetable ingredients, with base ingredients such as baru almonds.